The MYB transcription factor Emission of Methyl Anthranilate 1 stimulates emission of methyl anthranilate from Medicago truncatula hairy roots. (17th May 2019) - Pollier, Jacob; De Geyter, Nathan; Moses, Tessa; Boachon, Benoît; Franco‐Zorrilla, José M.; Bai, Yuechen; Lacchini, Elia; Gholami, Azra; Vanden Bossche, Robin; Werck‐Reichhart, Danièle; Goormachtig, Sofie; Goossens, Alain
Summary: Plants respond to herbivore or pathogen attacks by activating specific defense programs that include the production of bioactive specialized metabolites to eliminate or deter the attackers. Volatiles play an important role in the interaction of a plant with its environment. Through transcript profiling of jasmonate‐elicited Medicago truncatula cells, we identified Emission of Methyl Anthranilate (EMA) 1, a MYB transcription factor that is involved in the emission of the volatile compound methyl anthranilate when expressed in M. truncatula hairy roots, giving them a fruity scent. RNA sequencing (RNA‐Seq) analysis of the fragrant roots revealed the upregulation of a methyltransferase that was subsequently characterized to catalyze the O ‐methylation of anthranilic acid and was hence named M. truncatula anthranilic acid methyl transferase (MtAAMT) 1. Given that direct activation of the MtAAMT1 promoter by EMA1 could not be unambiguously demonstrated, we further probed the RNA‐Seq data and identified the repressor protein M. truncatula plant AT‐rich sequence and zinc‐binding (MtPLATZ) 1. Emission of Methyl Anthranilate 1 binds a tandem repeat of the ACCTAAC motif in the MtPLATZ1 promoter to transactivate gene expression. Overexpression of MtPLATZ1 in transgenic M. truncatula hairy roots led to transcriptional silencing of EMA1, indicating that MtPLATZ1 may be part of a negative feedback loop to control the expression of EMA1 . Finally, application of exogenous methyl anthranilate boosted EMA1 and MtAAMT1 expression dramatically, thus also revealing a positive amplification loop. Such positive and negative feedback loops seem to be the norm rather than the exception in the regulation of plant specialized metabolism. Significance Statement: Volatiles play an important role in the interaction of a plant with its environment. Here, we have identified a MYB transcription factor that is involved in the emission of the volatile compound methyl anthranilate in the model legume Medicago truncatula .